The Crisis is Gradually Being Overcome - Martin Gornig; Oliver Holtemöller; Stefan Kooths; Torsten Schmidt; Timo Wollmershäuser (Wirtschaftsdienst)
Abstract The leading economic research institutes have lowered their GDP growth forecast for 2021 from 3.7 % to 2.4 %. Weakening industrial production, which is suffering from supply bottlenecks, is particularly responsible for this. The global economy is recovering from the disruptions of the coronavirus pandemic, but only slowly, as vaccination progress varies across regions. Consumer prices increased sharply in 2021.